Nitrogen fixation and ammonia switch-off in the photosynthetic bacterium Rhodopseudomonas viridis. - Howard, K S (1983)
Rhodopseudomonas viridis ATCC 19567 grows by means of nitrogen fixation in yeast extract-N2 or nitrogen-free medium when sparged with 5% CO2 and 95% N2 in the light at 30 degrees C. Acetylene reduction assays for nitrogenase activity revealed an initially high level of activity during early-logarithmic growth phase, a lower plateau during mid- to late-logarithmic phase, and a dramatic reduction of activity at the beginning of the stationary phase. When viewed by electron microscopy, nitrogen-fixing R. viridis cells appeared to be morphologically and ultrastructurally similar to cells grown on nitrogen-rich media. Whole cells prepared under reducing conditions in the dark for electron spin resonance spectroscopy yielded g4.26 and g3.66 signals characteristic of the molybdenum-iron protein of nitrogenase. During growth on N2 in the absence of fixed-nitrogen sources, the nitrogenase activity of R. viridis measured by acetylene reduction stopped rapidly in response to the addition of NH4Cl as has been observed in other Rhodospirillaceae. However, unlike the nitrogenase of Rhodopseudomonas palustris or Rhodospirillum rubrum, which recover from this treatment within 40 min, the nitrogenase activity of R. viridis was not detectable for nearly 4 h.